Optimal treatment of asymptomatic patients with severe aortic stenosis: protocol of a prospective, multicentre, registry study - Yong Peng; Tian-Yuan Xiong; Mao Chen; Yuan Feng; Wei Xiong; Zhen-gang Zhao; Congying Xia; Yi-Ming Li; Liqiao Ma; Jiafu Wei (BMJ Open)
Introduction Decisions regarding the optimal timing of intervention for asymptomatic aortic stenosis (AS) are controversial. The study aims to identify potential risk factors for asymptomatic patients with severe AS that are associated with worse prognosis and to evaluate the benefits of early interventions for asymptomatic patients presenting with one or more additional risk factors.Methods and analysis This is a non-interventional, prospective, open-label, multicentre registry study across China. A total of 1000 patients will be enrolled and categorised as symptomatic or asymptomatic. The primary endpoint is the occurrence of all-cause mortality, stroke, acute myocardial infarction and heart failure-related hospitalisation at 1-year follow-up. In asymptomatic severe AS patients presenting with one or more risk factors, the occurrence rate of the primary endpoint between those who undergo transcatheter aortic valve replacement (TAVR) and those who do not will be compared. We will also compare the occurrence rate of the primary endpoint for asymptomatic severe AS patients with additional risk factors who undergo TAVR with those presenting with symptoms. This study is believed to provide additional evidence to help clinicians identify and refer severe AS patients who are asymptomatic but present with additional risk factors for early intervention of TAVR.Ethics and dissemination The study protocol has been approved by the local ethics committee of each participating site: West China Hospital, Sichuan University; Sir Run Run Shaw Hospital, Zhejiang University School of Medicine; Second Hospital of Hebei Medical University; Tianjin Chest Hospital; and First Affiliated Hospital of Nanchang University. All participants will provide written informed consent. Study results will be published through academic conferences and peer-reviewed journals.Trial registration This study was registered at the Chinese Clinical Trial Registry (https:// www.chictr.org.cn), with the registration number ChiCTR2200064853.